Population Viral Load, Viremia, and Recent HIV-1 Infections: Findings From Population-Based HIV Impact Assessments (PHIAs) in Zimbabwe, Malawi, and Zambia. (1st August 2021) - Farahani, Mansoor; Radin, Elizabeth; Saito, Suzue; Sachathep, Karampreet K.; Hladik, Wolfgang; Voetsch, Andrew C.; Auld, Andrew F.; Balachandra, Shirish; Tippett Barr, Beth A.; Low, Andrea; Smart, Theodore F.; Musuka, Godfrey; et al.
Abstract : Background: HIV population viral load (PVL) can reflect antiretroviral therapy program effectiveness and transmission potential in a community. Using nationally representative data from household surveys conducted in Zimbabwe, Malawi, and Zambia in 2015–16, we examined the association between various VL measures and the probability of at least one recent HIV-1 infection in the community. Methods: We used limiting-antigen avidity enzyme immunoassay, viral load suppression (VLS) (HIV RNA <1000 copies/mL), and antiretrovirals in the blood to identify recent HIV-1 cases. Results: Among 1510 enumeration areas (EAs) across the 3 surveys, 52, 036 adults aged 15–59 years resided in 1363 (90.3%) EAs with at least one HIV-positive adult consenting to interview and blood draw and whose VL was tested. Mean HIV prevalence across these EAs was 13.1% [95% confidence intervals (CI) 12.7 to 13.5]. Mean VLS prevalence across these EAs was 58.7% (95% CI: 57.3 to 60.0). In multivariable analysis, PVL was associated with a recent HIV-1 case in that EA (adjusted odds ratio: 1.4, 95% CI: 1.2 to 1.6, P = 0.001). VLS prevalence was inversely correlated with recent infections (adjusted odds ratio: 0.3, 95% CI: 0.1 to 0.6, P = 0.004). The 90-90-90 indicators, namely, the prevalence of HIV diagnosis, antiretroviral therapy coverage, and VLS at the EA level, were inversely correlated with HIV recency at the EA level. Conclusions: We found a strong association between PVL and VLS prevalence and recent HIV-1 infection at the EA level across 3 southern African countries with generalized HIV epidemics. These results suggest that population-based measures of VLS in communities may serve as a proxy for epidemic control.